Pengaruh Work-Life Balance dan Flexible Work Arrangement Terhadap Kinerja Karyawati Muslimah Konveksi - Saifullah, Fadhila (Universitas Islam Negeri Sunan Kudus, 2020)
This study aims to determine the effect of work-life balance and flexible work arrangement on employee performance, the type of research used is explanatory research with quantitative approach. Sample taken as many as 35 respondents. Data analysis use descriptive statistical analysis. Based on the results of the analysis showed that the variable work-life balance and flexible work arrangement didn’t affect the performance of employees as seen from the results of the t test to get a tcount of -1.258 and sig. of 0.218 (p>0.05) which shows that there is no influence between work-life balance on employee performance. And the t test results obtained a tcount of 2.625 and a sig. of 0.013 (p>0.05) which indicates that there is no influence between flexible work arrangement on employee performance. The adjusted R square value is only 0.282, it shows that the work-life balance and flexible work arrangement have an effect of 28.2% on the performance of employees and the rest 71.8% is influenced by other variables not included in this study.